Early Vascular and Functional Changes after Vitreoretinal Surgery: A Comparison between the Macular Hole and Epiretinal Membrane - Rossella D’Aloisio; Paolo Carpineto; Agbéanda Aharrh-Gnama; Carla Iafigliola; Luca Cerino; Marta Di Nicola; Annamaria Porreca; Lisa Toto; Rodolfo Mastropasqua (Diagnostics, 2021)
(1) Background: The aim of this observational comparative study was to investigate early retinal vascular and functional changes in patients undergoing vitreoretinal surgery for idiopathic epiretinal membrane (iERM) or macular hole (MH) using a widefield swept-source optical coherence tomography angiography (WSS-OCTA). (2) Methods: Forty one diseased eyes were enrolled in the study. Twenty three eyes with iERM diagnosis (ERM group) underwent 25-gauge vitrectomy with inner limiting membrane (ILM) and MER peeling, while eighteen eyes with MH (MH group) underwent 25-gauge vitrectomy with inverted flap technique. Functional and anatomical/perfusion parameters were evaluated pre- and postoperatively in all eyes by means of WSS-OCTA system, microperimetry (MP3), best corrected visual acuity assessment, central macular thickness (CMT) and MH diameter calculation. For each eye, 12 × 12 mm OCTA volume scans were acquired by a retinal specialist and a semi-automated algorithm was used for a quantitative vessel analysis of the superficial capillary plexus (SCP), deep capillary plexus (DCP) and choriocapillaris (CC). In detail, perfusion density (PD) of the SCP, DCP and CC was evaluated in four circles (one central in the macular area of 5 mm diameter; three midperiphery circles (temporal, superior and inferior) of 3 mm). In addition, the vessel length density (VLD) of the SCP and DCP for the same circles was quantified. (3) Results: In the MH group, PD of the SCP significantly increased in the macular area (p = 0.018) and in the superior ring (p = 0.016); PD of the DCP significantly increased in the macular area (p = 0.015) and in the superior and inferior ring (p = 0.016) 3 months after surgery. In the ERM group, PD of the SCP and DCP significantly increased in the macular area and superior ring, respectively (p = 0.001; p = 0.032), 3 months after surgery. During follow-up there was a significant improvement in terms of functional (Best corrected visual acuity, p = 0.007 and p = 0.029; microperimetry ((MP3) 10°, p = 0.003 and p = 0.004; MP3 2°, p = 0.028 and p = 0.003 in MH group and ERM group respectively) and anatomical parameters (CMT, p = 0.049 in ERM group; hole complete closure in MH group). (4) Conclusions: After vitreoretinal surgery, early retinal vascular and functional changes can be promptly observed and quantified to monitor and potentially predict surgery outcomes. Widefield OCTA devices allow for a detailed microvasculature analysis of retina and choriocapillaris in the macular area and in the periphery, showing a different behaviour of retinal sectors in two distinct vitreoretinal disorders.